Perlawanan Perempuan dalam Novel Penangsang Tembang Rindu Dendam dan Novel Pada Sebuah Kapal Kajian Feminisme Sosial - Widiarti, Melia; Supratno, Haris; Andriyanto, Octo Dendy (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The background of this research is the reality of gender injustice and marginalization of women that are still strongly reflected in Indonesian literary works. The purpose of this research is to identify the resistance strategies carried out by female characters in facing subordination, stereotypes, marginalization, and symbolic violence that are legitimized by patriarchal social, political, and cultural structures. The method used is descriptive qualitative with semiotic analysis and content analysis techniques, where the main data are narratives in the two novels that show the dynamics of injustice and women's resistance. The type of data used is in the form of text excerpts or narratives that describe women's resistance to the patriarchal system. The results of the study show that women's resistance in both novels is not always confrontational, but is also manifested through symbolic strategies, emotional solidarity, affirmation of the right to education, and negotiation of meaning in domestic and public spaces. Female characters such as Ratu Mas Nyowo, Ratu Kalinyamat, and Rani Suhita in Penangsang Tembang Rindu Dendam fight for their position and dignity amidst political intrigue and power, while Sri in Pada Sebuah Kapal displays a more personal and emotional resistance to household pressures and societal expectations. This research provides theoretical contributions to the development of feminist and semiotic studies of literature, by showing how women as active subjects are able to negotiate identity, role, and influence amidst the limitations of the patriarchal system. Socially, this research highlights the importance of awareness of gender injustice and women's resistance in society, which can inspire social change in a modern context.